Pendampingan Guru SMKS Prima Bakti Dalam Membuat Modul Praktek dan Trainer Kit Elektronika Dasar, Tangerang - Wildan, Muh; Purwaningtyas, Dian Anggraini; Eriyandi; Wahyudi, Johan; Roza, Febria; Ermawati, Leni Tri; Arafi , Thoriq (Jurnal Pengabdian Kepada Masyarakat, 2025)
Vocational school students are vocational schools that are at the forefront of the industrial world. This Community Service (PKM) activity was carried out based on concerns about the condition of several vocational schools with practical facilities that were still below standard. The responsibility of universities is not only to produce students but also to improve the surrounding area so that the benefits are also felt in society. The PKM scheme that will be implemented is an Assisted School-based Scheme (PKM-SB). PKM's partner is Prima Bakti Vocational School with a "B" or Very Good accreditation. Partners do not have adequate facilities for the Industrial Electronics Engineering major, especially for basic electronics lessons. Therefore, the activities that will be carried out will involve assisting Prima Bakti Vocational School teachers in creating practical modules and basic electronics trainer kits. The practical module is adapted to the curriculum and syllabus currently being implemented in schools for grade 9 students in Basic Electrical and Electronics subjects. The module in the form of a practical job sheet is a basic competency of knowledge and skills consisting of 14 experiments. The modules and trainer kit have been tested for their function properly and have been tested on students. The implementation of PKM activities also evaluated the level of satisfaction from PKM partners, namely productive teachers and the management of SMKS Prima Bakti school, with 100% satisfaction. The hope is that this PKM can boost the accreditation ranking and quality of human resources for graduating Prima Bakti Vocational High School students.